Genome-wide signatures of coevolution in parasitic and autotrophic plants - deRoux, Chris, author; Sloan, Dan, advisor; Forsythe, Evan, committee member; Borowiec, Marek, committee member (Colorado State University. Libraries, 2025)
Parasitism has repeatedly evolved in flowering plants, resulting in convergent genomic, metabolic, and morphological adaptations. Evolutionary Rate Covariation (ERC) analysis is a phylogenomic method used to uncover gene pairs whose functional interactions are under shared selection pressures. In this study, we applied the ERCnet pipeline to a paired sample of parasites and autotrophic relatives to investigate patterns of gene coevolution common to trophic mode transitions. Few networks of genes sharing ERC exhibited trophic-mode-driven differences in evolutionary rates, suggesting divergent selection pressures on shared interactions. Gene Ontology (GO) analysis yielded underrepresentation of plastid-related genes in coevolving networks. Meanwhile, two smaller networks highlighted the slow evolution of developmental and fatty acid metabolism genes in parasites. Covarying genes involved in the WUSCHEL/CLAVATA3 (WUS/CLV3) signaling pathway, key to shoot development, evolved slowly in parasites, implicating them in body plan reorganization. Additionally, genes involved in fatty acid metabolism were overrepresented in a slow-evolving parasite cluster, hinting at parasite dependence on conserving this pathway while losing photosynthetic plastid functions. These results indicate conservation of gene coevolution patterns between the two trophic modes, with a few notable exceptions. Expanding ERC analysis of parasitic plants to include more species could provide greater insight into divergent and conserved networks of gene interactions.